Optimization of Port Layout to Determine Greenhouse Gas Emission Gaps - Derpich-Contreras, I (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Ports are of great strategic importance for a country. Nowadays, compliance with environmental requirements is required, forcing the migration towards clean energies. Therefore, it is necessary for emerging ports, as those in developed countries, to incorporate in their policies the use of electric power in the machinery that moves containers in the terminals. To learn how the problem is addressed in other countries, an extensive bibliographic review is presented. Then, the energy policies and criteria of a group of ports in an emerging country and a European port are studied. Subsequently, in order to determine the gaps between the ports investigated, the layout of the cargo yard of each of the terminals is optimized; the emissions of Carbon Dioxide (CO2) and other Greenhouse Gases (GHG) gases are calculated; and finally, the decrease in emissions when switching from diesel to electricity is estimated. The strategic and operational gaps related to energy management between the emerging and developed countries are discussed. It is concluded that research is needed to investigate how these initiatives impact the city and improve other sustainable aspects. © 2022 by the authors.